فعالية التحصيل الجبري في تحسين الحصيلة الجبائية دراسة حالة مديرية الضرائب إيليزي(2014-2021) - مسعودي, علي; عياشي عمر, علي (جامعة الوادي - University of Eloued, 2023)
This study aims to know how to apply follow-up procedures and their repercussions on improving tax collection or not, in the Tax Directorate of the State of Illizi, during the extended period (2014- 202) in light of the reluctance of some taxpayers to pay their tax dues. Where the study concluded with the ineffectiveness and stability of forced collection for several reasons, including the difficulty of applying all follow-up procedures and limiting them to alerting and notifying what is owed by others (ATD), and the large size of the collection remains, as well as those related to the negative behavior of the taxpayer, which was confirmed by the Accounting Council in Its annual report for the year 2018.
The effectiveness of algebraic collection in improving the fiscal outcome Elysee Tax Directorate Case Study (2014-2021)
مقال
Keywords: تحصيل جبري، تحصيل ودي، حصيلة ضريبية.